Distinguishing the Language of Destructive Cults from the Language of Mainstream Religion: Corpus Analyses of Sermons - T. Palayon, Raymund; Watson Todd, Richard; Vungthong, Sompatu (rEFLections, 2022)
The language of religious leaders expressed in their sermons characterizes the social characteristics of their groups. Over the past decades, most studies into cults specifically destructive cults and mainstream religion have mainly focused on their social-psychological characteristics with limited applicability to other religious groups. In this study, corpus-based methods were applied to the sermons of the leaders of two destructive cults (namely, Peoples Temple led by Jim Jones and Heaven’s Gate led by Marshall Applewhite) and the sermons of mainstream religious groups represented by Baptist preachers to distinguish the language between dangerous and beneficial religious groups based on the patterns of key linguistic features. The methodological process includes keyness analyses (namely, keyword analysis, key semantic tag analysis, and key part-of-speech analysis) and multidimensional analysis. The results from a keyness perspective show that the destructive cult sermons promote non-religious concepts with the use of othering, intensification, and strong elaboration. For the mainstream sermons, they uphold religious concepts for life development with the use of personal involvement and moderate elaboration. The results from a text dimension perspective show that the language of destructive cults and the language of mainstream religion displayed in their sermons are both persuasive and elaborative. However, the language of destructive cults is more persuasive and elaborative than the language of mainstream religion. The findings may serve as a basis for how to recognize the potential detrimental and beneficial characteristics of religious groups based on their language.